Transforming Nigeria Food System: The Role of Agroforestry - G. I. Otiwa; B. O. Adaaja; E. Y. Zaman; A. Z. Haruna; E. O. Oloyede; N. N. Akemien (Journal of Applied Sciences and Environmental Management, 2023)
It has been generally established that the global food system needs to be transformed urgently, in order to meet the growing demand for food, feed and fodder. Agroforestry is a type of farming system that combines trees/shrubs with crops with the objective of enjoying a mutual benefit that enhances productivity, profitability and biodiversity, which at the moment is unpopular in Nigeria. Therefore the objective of this paper is to provide relevant information on the role of agroforestry in transforming the Nigerian food system. Some of the agroforestry technologies which can be used to achieve its mutual benefit include taungya system, home garden, alley cropping, improved fallow, woodlots, live fences, fodder banks, orchards or tree gardens, windbreaks, shelterbelts, trees on pasture and apiculture with trees. Planting trees as a component of crop farming is a smart way to achieve multiple purposes with a single enterprise. Planting multipurpose trees in a world affected by climate change can decelerate the negative impact of anthropogenic cause of climate change, while providing food for humanity. Hence, the paper also review the roles of agroforestry in the global fight against climate change, while also ensuring food security through food system transformation.